Can Smoking Cause Differences in Urine Microbiome in Male Patients With Bladder Cancer? A Retrospective Study - Ma, Wenchao; Zhang, Wentao; Shen, Liliang; Liu, Ji; Yang, Fuhang; Maskey, Niraj; Wang, Hong; Zhang, Junfeng; Yan, Yang; Yao, Xudong (Frontiers in Oncology, 2021)
Abstract Background: Tobacco smoking is a carcinogen for many cancers including bladder cancer. Microbiota is involved in the occurrence, development and treatment of tumors. We explored the composition of male urinary microbiome and the correlation between tobacco smoking and microbiome in this study. Methods: Alpha diversity, principal component analysis(PCA) and Adonis analysis, linear discriminant analysis(LDA) coupled with effect size measurements and PICRUSt function predictive analysis were used to compare different microbiome between smokers and non-smokers in men. Results: There were 26 qualified samples included in the study. Eleven of them were from healthy men and the others were from men with bladder cancer. Simpson index and PCA analysis between smokers and non-smokers were no difference in healthy men. However, the abundance of Bacteroidaceae, Erysipelotrichales, Lachnospiraceae, Bacteroides and so on in the urinary tract of smokers is much higher than that of non-smokers. In bladder cancer patients, the alpha diversity in smokers was higher than non-smokers and PCA analysis showed that tobacco smoking plays a vital role in urinary tract microbial composition. Conclusion: This study analyzed the composition of urinary tract microbiome in healthy men and men with bladder cancer. It also explored the effects of smoking on urinary tract microbiota.